2000
DOI: 10.3758/bf03198561
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic judgment of cause in a relative validity paradigm

Abstract: We report three experiments in which we tested asymptotic and dynamic predictions of the Rescorla-Wagner(R-W) model and the asymptotic predictions of Cheng's probabilistic contrast model (PCM) concerning judgments of causality when there are two possible causal candidates. We used a paradigm in which the presence of a causal candidate that is highlycorrelated with an effect influences judgments of a second, moderately correlated or uncorrelated cause. In Experiment I, which involved a moderate outcome density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 21 publications
4
30
0
1
Order By: Relevance
“…It has been repeatedly demonstrated that causal judgments deviate from contingency in a number of experimental preparations (Allan & Jenkins, 1983;Baker, Vallée-Tourangeau, & Murphy, 2000;Lober & Shanks, 2000;Perales & Shanks, 2003). In light of the previous argument, however, this does not imply that judgments deviate from normativity.…”
Section: Contingencymentioning
confidence: 51%
“…It has been repeatedly demonstrated that causal judgments deviate from contingency in a number of experimental preparations (Allan & Jenkins, 1983;Baker, Vallée-Tourangeau, & Murphy, 2000;Lober & Shanks, 2000;Perales & Shanks, 2003). In light of the previous argument, however, this does not imply that judgments deviate from normativity.…”
Section: Contingencymentioning
confidence: 51%
“…When considered in the context of related research, discounting and more complex causal reasoning theories (e.g., Cheng 1997) lack parsimony (e.g., van Osselaer and Alba 2000). In addition, other authors have pointed out shortcomings of causal reasoning in general as an explanation of cue-interaction phenomena (e.g., Baker, Vallée-Tourangeau, and Murphy 2000;Lober and Shanks 2000).…”
Section: Some Additional Observationsmentioning
confidence: 97%
“…Competition with contextual cues can have powerful effects on learning (Baker et al, 1996;Baker et al, 2000;Murphy et al, 2005). Msetfi and colleagues (2005) showed that individual differences in judgments of causal control, seemingly related to depressive symptoms, were themselves related to context learning.…”
Section: Speed Of Learningmentioning
confidence: 99%